A evidenciação dos objetivos de desenvolvimento sustentável: um estudo nos portos e terminais portuários brasileiros - DINIZ, Natália Viana (2023)
The aim of this study was to analyze the disclosure of the Sustainable Development Goals in the reports published by the Brazilian ports and port terminals with the highest cargo throughput. This is an exploratory and descriptive study, which initially identified the Brazilian ports and port terminals with the highest cargo throughput and the publication of non-financial reports by the port authorities and the companies that own the port terminals. This was followed by a qualitative analysis, through a systematic literature review, of the SDGs most addressed by the port sector and the maritime industry in the scientific literature, as well as a quantitative analysis of publication trends, based on a bibliometric study. Finally, a content analysis was carried out of the integrated and annual sustainability reports published by the selected ports and port terminals, to identify the main sustainable practices aligned with SDG 9 (industry, innovation and infrastructure), 13 (action against global climate change) and 14 (life on the water). The results of the study highlighted the direction of the Brazilian port sector in developing sustainable mechanisms mediated by technologies such as radars and cameras, as well as encouraging investment in research and development, reinforcing the commitment to SDG 9. Likewise, initiatives that promote the reduction of greenhouse gas (GHG) emissions, more efficient operations and that help with the energy transition were highlighted, as well as the sector's commitment to SDG 13. However, a small number of practices focused on SDG 14, related to life on the water, were observed, even though this SDG is one of the most aligned with the port's core business, with monitoring programs standing out. It is concluded that the results of this research provide the main sustainable practices aligned with SDGs 9, 13 and 14 applied by Brazilian ports and port terminals, fostering the debate on port sustainability and reinforcing the importance of applying the SDGs as an instrument for achieving an economically and socially sustainable society.